Devoted to Death: Santa Muerte, the Skeleton Saint - Chesnut, R. Andrew (Oxford University Press USA - OSO, 2012)
R. Andrew Chesnut offers a fascinating portrayal of Santa Muerte, a skeleton saint whose cult has attracted millions of devotees in the past eight years. As a personification of death, the Grim Reapress has become one of the most popular and powerful saints on both the Mexican and American religious landscapes. Although condemned as satanic by both Catholic and Protestant churches, this folk saint's supernatural powers appeal to millions of Mexican citizens and Central American and Mexican immigrants.